The effect of the Industry Growth Level on the need of Innovation in organizations: Case study : The economic inflation in cell phone service industry in Algeria - Yacine BOUBAKEUR; Kahina Slimani (Journal of Excellence for Economics and Management Research, 2017)
The economic inflation is one of the most important indicators of the Industrial growth, It expresses on uncertain environment, weakness and Instability. So, The economic writers used to point out about an Inverse relationship between the level of economic inflation and the growth inside industry. So that, the Continuous height of prices drives to a height of this inflation the one that takes to a weakness of the industry. Here, the organization are forced to find out a new paths to improve it’s situation in industry. Innovation is one of those suggested solutions that may be taken, and the issue that happened in cell phone services industry in Algeria, Because of the long height level of prices particularly in the beginning of product lice cycle.